Vertical marginal gap evaluation of PEEK and Zirconia crowns using extra-oral scanner and CAD/CAM systems (An Invitro study). - Raz Ali Aula; Jawad Mohammed Mikaeel (Erbil Dental Journal)
Background and objective: Selecting a material with lower marginal gap is the key factor for a successful dental prosthesis. With less marginal gap of the crown the aggregation of bacterial plaque at the gingival margins, that result in periodontal diseases and secondary caries could be limited. Methods: A mandibular right first molar of a sound tooth was prepared for the reference model according to the tooth preparations guideline with a heavy chamfer finishing line for full zirconia and Polyetheretherketone (PEEK) coverage. Digital impression technique with extraoral scanner was used for scanning and taking impression of the reference model, ten crowns in each group were designed and milled using CAD/CAM systems. The vertical marginal gap between the crown's margin and the finishing line was measured for each crown on the reference model with the aid of a stereomicroscope in 160x. Results: The average (mean) for the marginal gap of proximal, buccal and lingual surfaces of both PEEK, and zirconia materials were: 409.097 μm, 112.869 μm, 198.563 μm, for PEEK and, 105.085 μm, 27.659 μm, 45.135 μm for zirconia respectively. Statistical analysis using t-test for two independent samples revealed that PEEK material showed a significantly higher marginal gap than z. irconia material. Conclusion: PEEK crowns had a higher marginal gap than clinically acceptable limit, while zirconia crowns exhibited much lower measurements.